The theory and practice gap in participatory communication - Muturi, Nancy W.; Mwangi, Samuel (My University, 2011)
This article addresses the application of the participatory approach in a campaign that addressed gender-based violence in the Caribbean. The project brought together key funding agencies in the region and seven local women's organisations to address the increasing rate of violence against women in Jamaica. Based on information gathered qualitatively from in-depth interviews, focus group discussions and project documents, the article delineates the problems that subvert well-intentioned participatory communication projects when executed using models that otherwise sound good on paper. The article makes key contributions to participatory approach theory and practice by identifying two new areas for future studies to explore, namely the motivations and gratifications of project participants as important predictors of the success or failure of development projects, and the need to focus on a society's value system and its compatibility with the philosophical assumptions behind the participatory approach.
Keywords: Participatory communication; Gender-based violence; Qualitative research; Caribbean; Development communication; Theory application